Melodrama after the tears new perspectives on the politics of victimhood - Loren, Scott 1971-; Metelmann, Jörg 1970- (Amsterdam University Press, 2016)
Melodrama, it is said, has expanded beyond the borders of genre and fiction to become a pervasive cultural mode. It encompasses distinct signifying practices and interpretive codes for meaning-making that help determine the parameters of identification and subject formation. From the public staging of personal suffering or the psychologization of the self in relation to consumer capitalism, to the emotionalization and sentimentalization of national politics, contributions to this volume address the following question: If melodramatic models of sense-making have become so culturally pervasive and emotionally persuasive, what is the political potential of melodramatic victimhood and where are its political limitations? This volume represents both a condensation and an expansion in the growing field of melodrama studies. It condenses elements of theory on melodrama by bringing into focus what it recognizes to be the locus for subjective identification within melodramatic narratives: the victim. On the other hand, it provides an expansion by going beyond the common methodology of primarily examining fictive works - be they from the stage, the screen or the written word - for their explicit or latent commentary on and connection to the historical contexts within which they are produced. Inspiration for the volume is rooted in a curiosity about melodramatic forms purported to increasingly characterize aspects of both the private and the social sphere in occidental and western-oriented societies
Title from publisher's bibliographic system (viewed on 22 Feb 2021)
Cultures of Suffering and Cinematic Identities -- Melodrama and Victimhood: Modern, Political and Militant / Thomas Elsaesser -- When Is Melodrama "Good"? Mega-Melodrama and Victimhood / Linda Williams -- Melodrama and War in Hollywood Genre Cinema / Hermann Kappelhoff -- Race Interactions: Film, Melodrama, and the Ambiguities of Colorism / Christof Decker -- The Purloined Letter: Ophuls after Cavell / Ulrike Hanstein -- Modernity and the Melodramatic Self -- The Melodrama of the Self / Eva Illouz -- Rousseau's Nightmare / Vincent Kaufmann -- "Emotional Suffering" as Universal Category? Victimhood and the Collective Imaginary / Jörg Metelmann -- Collective Traumas and National Melodramas -- Legacies of 9/11 -- Introduction to W.J. T. Mitchell, "The Abu Ghraib Archive" / Scott Loren -- The Abu Ghraib Archive / W.J.T. Mitchell -- The Melodramatic Style of American Politics / Elisabeth Anker -- Tears of Testimony: Glenn Beck and the Conservative Moral Occult / Scott Loren -- Holocaust Legacies -- The Cultural Construction of the Holocaust Witness as a Melodramatic Hero / Amos Goldberg -- Nation and Emotion: The Competition for Victimhood in Europe / Ulrich Schmid
Keywords: Melodrama in motion pictures; Melodrama / History and criticism; Opfer -- Sozialpsychologie, Motiv; Melodrama -- Film; Aufsatzsammlung